A Synthesis and Evaluation of Geosynthetic-Reinforced Base Layers in Flexible Pavements- Part I. Issue 6 (1997) - Perkins, S.W.; Ismeik, M.
Abstract : In recent years, geosynthetics have been proposed and used as reinforcement in the base course layer of flexible pavements for the purpose of improving performance and/or to allow for the reduction of base course thickness. Much of the pioneering work with geosynthetic-reinforced unpaved roads on very soft subgrades has indicated that appreciable deformation of the roadway surface is necessary before the reinforcement qualities of the geosynthetic can be realized. It may be expected that this same condition is necessary in a paved road, thereby obviating the practical use of geosynthetics as reinforcement. It appears that this view has gained acceptance in the research and practice oriented engineering communities. The purpose of this paper is to provide a synthesis and evaluation of the literature focusing on this application. The paper focuses on studies involving laboratory-scale experiments using stationary cyclic loads or moving wheel loads and field studies using controlled vehicle loads or random traffic loads. The majority of the studies reviewed indicate that appreciable improvement can be realized by proper placement of a geosynthetic in the base course of a flexible pavement and that improvement is seen over the entire service life of the pavement and not only for conditions of excessive surface deformation.